2014
DOI: 10.5935/abc.20140197
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Doppler Echocardiographic Study of Indeterminate Form of Chagas Disease

Abstract: BackgroundPatients with indeterminate form of Chagas disease/cardiac normality (ICD/CN) exhibited normal electrocardiograms and chest X-rays; however, more sophisticated tests detected some degree of morphological and functional changes in the heart.ObjectiveTo assess the prevalence of systolic and diastolic dysfunction of the right ventricle (RV) in patients with ICD/CN.MethodsThis was a case–control and prevalence study. Using Doppler two-dimensional echocardiography (2D), 92 patients were assessed and divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…However, early abnormalities have been described even in the indeterminate form, such as shortening of the RV isovolumetric contraction time or low RV s 0 on Doppler tissue imaging. 117,118 Moreover, RV Tei index provides incremental prognostic information to that of more traditional risk factors, such as New York Heart Association functional class and LV function. 116 The value of RV strain is still unclear in ChD.…”
Section: Vc Rv Functionmentioning
confidence: 99%
“…However, early abnormalities have been described even in the indeterminate form, such as shortening of the RV isovolumetric contraction time or low RV s 0 on Doppler tissue imaging. 117,118 Moreover, RV Tei index provides incremental prognostic information to that of more traditional risk factors, such as New York Heart Association functional class and LV function. 116 The value of RV strain is still unclear in ChD.…”
Section: Vc Rv Functionmentioning
confidence: 99%
“…Moreover, in this study, only patients with some degree of left ventricle dilatation or systolic dysfunction were included, which, per se, makes the investigational task of finding isolated RV early involvement unfeasible. Furtado et al also investigated the prevalence of RV systolic and diastolic dysfunction including its global performance index in a group of 60 subjects without evidence of cardiac disease by conventional diagnostic methods [ 49 ]. In contrast to the results of Nunes et al, the authors found a 26% prevalence of RV systolic dysfunction when using tissue Doppler systolic tricuspid velocity wave (S′).…”
Section: Evidence Of Right Ventricle Involvement In Chagas Diseasementioning
confidence: 99%
“…Other publications also addressed the potential of echocardiographic conventional parameters such as S ′, TAPSE, and MPI to detect right ventricular dysfunction in more advanced stages of disease and symptomatic patients [ 69 ]. Some publications also endorsed the ability of echocardiographic parameters to detect right ventricle dysfunction even in patients with the indeterminate form of the disease using tissue Doppler techniques [ 49 , 70 ]. However, using myocardium performance index (MPI), investigators were not able to differentiate patients with the indeterminate form of CD from controls [ 49 ].…”
Section: Current Imaging Evaluation Of the Right Ventricle In Cd: mentioning
confidence: 99%
See 1 more Smart Citation
“…Nossos resultados mostram acometimento precoce dessa câmara cardíaca, corroborando achados prévios de estudos experimentais e estudos clínicos que utilizaram diferentes métodos de imagem. Um estudo com ecocardiografia demonstrou valores reduzidos de mudança fracional da área do ventrículo direito em pacientes com a forma indeterminada da doença de Chagas em comparação a um grupo controle(101). Estudos anteriores utilizando ventriculografia radioisotópica demonstraram envolvimento do ventrículo direito em fases iniciais da evolução da doença de Chagas, mesmo na presença de função sistólica normal do ventrículo esquerdo(66,102).…”
unclassified